Modificação superficial de nanopartículas de óxido de ferro por poli(ácido aspártico) reticulado - Vega Chacon, Jaime Ricardo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Magnetic nanoparticles of iron oxide have been intensively investigated for biomedical applications due to their magnetic properties and dimensions which are smaller than the size of cells. The surface of iron oxide nanoparticles must be modified to obtain colloidal stability in water, biocompatibility and allow the formation of linkages with molecules with biological activity. Poly(aspartic acid) is obtained by basic hydrolysis of polysuccinimide, the polymer is water soluble, biodegradable and biocompatible, due to these features, the polymer attractive for biomedical applications. Poly(aspartic acid) hydrogel is sensitive to environmental pH, when the pH of the environment changes, the hydrogel is subjected to a change in volume. This work consists in the surface modification of magnetite nanoparticles with poly(aspartic acid) hydrogel, forming a multifunctional system responsive to an external magnetic field and the environmental pH, and with the necessary characteristics for applications in biomedicine. The magnetite nanoparticles were synthesized by coprecipitation method and polysuccinimide by polycondensation method. The surface modification of the nanoparticles is developed in the following steps: (1) coating the surface with silica functionalized with amine groups, (2) coating with chemically cross-linked polysuccinimide, (3) basic hydrolysis of the cross-linked polysuccinimide to obtain the poly(aspartic acid) hydrogel on the surface of magnetic nanoparticles. The obtained products were analyzed by the following techniques: X-ray diffraction, diffuse reflectance infrared spectroscopy, hydrogen-1 nuclear magnetic resonance spectroscopy, dynamic light scattering, electrophoretic mobility (zeta potential) and transmission electron microscopy. The influence of the concentrations of the reactants in the dimensions of the multifunctional system was evaluated. The hydrodynamic diameter of the...

Nanopartículas magnéticas de óxido de ferro tem sido intensivamente investigadas para aplicações em biomedicina devido às propriedades magnéticas e as suas dimensões as quais são menores que os tamanhos das células. A superfície das nanopartículas de óxido de ferro deve ser modificada para obter estabilidade coloidal em água, obter biocompatibilidade, e permitir a formação de ligações com moléculas com atividade biológica. O poli(ácido aspártico) é obtido da hidrólise básica da polissuccinimida, é um polímero solúvel em água, biodegradável e biocompatível, devido a estas caraterísticas é atrativo para aplicações em biomedicina. Hidrogél de poli(ácido aspártico) é sensível ao pH do ambiente, quando o pH do meio ambiente é alterado, o hidrogel é submetido a uma variação de volume. O presente trabalho consiste na modificação superficial de nanopartículas de magnetita com hidrogél de poli(ácido aspártico), formando um sistema multifuncional responsivo a um campo magnético externo e ao pH do ambiente, e com as características necessárias para aplicações em biomedicina. As nanopartículas de magnetita foram sintetizadas pelo método de coprecipitação e a polissuccinimida pelo método de policondensação. A modificação superficial destas nanopartículas se desenvolveu nas seguintes etapas: (1) revestimento da superfície com sílica funcionalizada com grupos amina, (2) revestimento com polissuccinimida reticulada químicamente, (3) hidrólise básica da polissuccinimida reticulada para obter o hidrogel de poli(ácido aspártico) na superfície das nanopartículas magnéticas. Os produtos obtidos foram analisados pelas seguintes técnicas: difratometria de raios X, espectroscopia no infravermelho por refletância difusa, espectroscopia de ressonância magnética nuclear de hidrogênio, espalhamento dinâmico de luz, mobilidade eletroforética (potencial...
Keywords: Nanopartículas; Materiais magneticos; Polimeros na medicina; Nanogéis; Magnetita; Nanoparticles